2022
DOI: 10.3389/fsoc.2021.792198
|View full text |Cite
|
Sign up to set email alerts
|

Why so Few, Still? Challenges to Attracting, Advancing, and Keeping Women Faculty of Color in Academia

Abstract: From its earliest beginnings, the university was not designed for women, and certainly not for women of color. Women of color in the United States are disproportionately under-represented in academia and are conspicuous by their absence across disciplines at senior ranks, particularly at research-intensive universities. This absence has an epistemic impact and affects future generations of scholars who do not see themselves represented in the academy. What are the barriers to attracting, advancing, and retaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 85 publications
1
42
0
Order By: Relevance
“…These findings are reflective of dental faculty overall, but disparities exist with women underrepresented in senior leadership roles. 24 Some of the gender inequities described in this cross‐sectional study may worsen the barriers for women breaking the “glass ceiling” and achieving senior faculty administrative positions in academia. 25 …”
Section: Discussionmentioning
confidence: 92%
“…These findings are reflective of dental faculty overall, but disparities exist with women underrepresented in senior leadership roles. 24 Some of the gender inequities described in this cross‐sectional study may worsen the barriers for women breaking the “glass ceiling” and achieving senior faculty administrative positions in academia. 25 …”
Section: Discussionmentioning
confidence: 92%
“…It reflects inadequacies in national datasets in delimiting data by subgroups (e.g., gender by race), which often have low sample sizes ( Gruber et al, 2020 ). Our broad focus limits generalizability to women with intersectional identities (see Fox Tree and Vaid, 2022 ; Morimoto, 2022 ; Wong et al, 2022 ).…”
Section: Focus Methodology and Data Sourcesmentioning
confidence: 99%
“…Despite these successes, with ADVANCE projects primarily focused on theoretical frameworks to address gender equity, early ADVANCE projects were criticized for implicitly or de facto targeting and thus benefiting white women (Hunt et al, 2012 ; Armstrong and Jovanovich, 2017 ; Fox Tree and Vaid, 2022 ). Indeed, studies showed that while white women were beginning to make equity gains in academic STEM fields, women of color lagged behind (Hirshfield and Tiffany, 2012 ; McQuillan and Hernandez, 2021 ), particularly black women (Snyder et al, 2016 ; Buchanan, 2020 ; Fox Tree and Vaid, 2022 ). In the social sciences, this is quite noteworthy, with less racial and ethnic diversity in these fields than in men dominated fields of engineering and biomedicine (Hur et al, 2017 ).…”
Section: The First Generation Of Advance: From a Program For Women To...mentioning
confidence: 99%
“…Illuminating how gender inequities were not independent of or simply additive to other barriers to success in the academy, research shows that BIPOC women are chronically underrepresented in academia generally, and particularly in STEM fields (Li and Koedel, 2017 ; National Science Foundation [NSF], 2019 ). Indeed, psychology has the highest proportion of White faculty of the social sciences (Fox Tree and Vaid, 2022 ).…”
Section: The Second Generation Of Advance: Gender Equity and Intersec...mentioning
confidence: 99%
See 1 more Smart Citation